(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
They have a number of advantages compared with other information technology training, as they allow: to improve the process of organic combination of traditional forms and methods of education with innovation; implement training, information, games, modeling, design and analysis functions; general didactic perform such principles as the visibility, accessibility, difficulty feasible, system, transition from education to self-education,positive emotional background of training, between theory and practice.